PERBEDAAN KADAR GULA DARAH PADA PASIEN SKIZOFRENIA YANG MENGGUNAKAN OBAT HALOPERIDOL DAN RISPERIDON DI RSJ. PROF. DR. M. ILDREM - ZAHRAH SAFIRA; NANDA SARI NURALITA; DAPOT PARULIAN GULTOM; MELVIANA LUBIS (JURNAL ILMIAH MAKSITEK, 2021)
Schizophrenia is a severe mental disorder that often occurs in the world. Current treatments for schizophrenia are typicalantipsychotics and atypical antipsychotics. Typical antipsychotics such as haloperidol, chlorpromazine, sulpirid, andthioridazine, and atypical antipsychotics such as risperidone, and atypical antipsychotics such as risperidone, clozapine,olanzapine and zipracidone. In the long term use of the drug can cause extrapyramidal symptoms, metabolic disorders suchas increased blood glucose levels. To determine differences in blood glucose levels in schizophrenic patients usinghaloperidol and risperidone at the mental hospital. Prof. Dr. M. Ildrem Medan which took from September to December 2019.This study is a non-paired numerical analytic study with a non- probability sampling technique that was carried out using ablood sugar level check tool during easy touch. The number of samples used was 46 schizophrenic patients, of which 23people took the drug haloperidol, and 23 people took the drug risperidone. Then performed an analysis with the Mann-Whitney test. The Mann-Whitney test results showed that there were significant differences between the use of haloperidoland risperidone drugs in schizophrenic patients with a P value of 0.001 (p <0.05). Risperidone drug use is higher riskcompared with haloperidol drugs. The use of risperidone has a significant difference with haloperidol on blood glucose levelswhen in schizophrenia patients.